150 years of quantum many-body theory : a festschrift in honour of the 65th birthdays of John W. Clark, Alpo J. Kallio, Manfred L. Rising, Sergio Rosati : UMIST, Manchester, UK, July 10-14, 2000 - Bishop, R. F. (Raymond F.); Gernoth, Klaus A.; Walet, Niels R. (Series on advances in quantum many-body theory, 2001)
In July 2000 a conference was held to honour the 65th birthdays of four of the leading international figures in the field of quantum many-body theory. The joint research careers of John Clark, Alpo Kallio, Manfred Ristig and Sergio Rosati total some 150 years, and this festschrift celebrated their achievements. These cover a remarkably wide spectrum. The topics in this book reflect that diversity, ranging from formal aspects to real systems, including nuclear and subnuclear systems, quantum fluids and solids, quantum spin systems and strongly correlated electron systems. The book collects more than 30 invited contributions from eminent scientists, chosen both from among the participants at the conference and from colleagues who were unable to attend but nevertheless wished to contribute. To match the high standing of the honourees, the articles are of an exceptionally high quality. Together they provide a vivid overview of current work across the spectrum of quantum many-body theory.